TPACK CALON GURU DALAM PROSES PEMBELAJARAN MATEMATIKA SECARA DARING - Liknin Nugraheni; Erlin Ladyawati; Moh. Syukron Maftuh (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
The role of the teacher is one of the most important aspects or factors that impact learning success. As a result, prospective teachers must have technical pedagogical content knowledge (TPACK) skills, as these are the integration of information and communication technology (ICT) with content knowledge of mathematics, pedagogy, and knowledge of students. The subjects in this study were students or prospective mathematics education teachers who had obtained theories regarding mathematical content, pedagogy, student knowledge, and technology, but they lacked experience in integrating these knowledges. As a result of the study, students are better equipped to integrate technology with mathematical curriculum, pedagogy, and student understanding.